Using a new programme (THERCOM) to predict thermal comfort as a base to design energy efficient buildings - Al-Khatri, Hanan; Gadi, Mohamed (GIAP Journals, 2014)
A strong relationship relates the thermal comfort and the consumption of energy, especially in the hot arid climate where the installation of HVAC systems is unavoidable. In fact, it has been reported that the HVAC systems are responsible for consuming huge amounts of the total energy used by the buildings that can globally reach up to 40% of the total primary energy requirement. The future estimations indicate that the energy consumption is likely to continue growing in the developed economies to exceed that of the developed countries in 2020. Under these situations, it seems that the shift towards more energy efficient buildings is not an option. Because part of any successful environmental design is to understand the potentials of the site, the proposed programme (THERCOM) assists in weighing the indoor and outdoor thermal comfort in different climates in order to provide better understanding of the site environment as well as testing the thermal comfort chances of the initial concepts.